DETERMINAN ENVIRONMENTAL DISCLOSURES PERUSAHAAN MANUFAKTUR DI INDONESIA DAN MALAYSIA - Isnani Fashikhah; Evi Rahmawati; Hafiez Sofyani (Jurnal Akuntansi Indonesia, 2018)
The study aims to examine the influence of corporate governance mechanism, company size and financial performance towards environmental disclosures in manufacturing companies listed in Indonesia Stock Exchange and Bursa Malaysia period 2016.The variables examined in this study are managerial ownership, size of the board of commissioners, company size, and liquidity. The research used purposive sampling method, obtained from 59 Indonesia manufacture companies and 63 Malaysia manufactures companies. The examination used multiple regression analysis and independent sample t test. The result of the research:1) The managerial ownership had negative influence towards environmental disclosures in Indonesia, but it had positive influence in Malaysia, 2) The size of the board of commissioners had positive influence towards environmental disclosures in Indonesia, but it did not have influence in Malaysia, 3) The size of the company did not have influence towards environmental disclosures in Indonesia, but it had positive influence in Malaysia,4) The liquidity had negative influence towards environmental disclosures in Indonesia, but it had positive influence in Malaysia, and5) There was difference in the level of environmental disclosures in Indonesia and in Malaysia.